Determinants of hemoglobin variability in stable peritoneal dialysis patients - VELİOĞLU, ARZU; AŞICIOĞLU, EBRU; ARIKAN, İZZET HAKKI; KOÇ, MEHMET; TUĞLULAR, ZÜBEYDE SERHAN (SPRINGER, 2014)
Significant within-patient hemoglobin (Hb) level variability is well recognized in particularly hemodialysis patients. Several factors such as hospitalizations, intercurrent diseases and IV iron therapy are found to be related to Hb variability (Hb-var). In this observational study, we aimed to identify predictors and outcome of Hb-var in peritoneal dialysis (PD) patients without hospitalization, intercurrent disease and IV iron therapy during the study period. All patients were in the maintenance phase of short-acting erythropoiesis-stimulating agents (ESAs) therapy. The target range of Hb was 11-12 g/dL according to KDOQI Guidelines in 2007. The desired range of Hb was 11-12.5 g/dL. Patients' demographic and laboratory data were collected at baseline. Atherosclerotic disease was assessed using carotid intima-media thickness (CIMT). We assessed Hb variability with various methods using SD Hb(mean), SD Hb(range) and the velocity of Hb change. Hb deflect(positive), Hb deflect(negative), Hb values and ESA dosing were recorded monthly for 6 months. This study included 50 prevalent PD patients (mean age 46.9 +/- A 13.7 years, 25 women). The mean velocity of Hb change was negatively correlated with age and positively correlated with frequent ESA dose changes. Higher albumin and residual renal function (RRF) were also positively correlated with Hb deflect(positive). Patients with CIMT a parts per thousand yen0.7 cm had lower SD Hb range compared to CIMT < 0.7 cm. Cumulative survival was better in patients with Hb levels consistently a parts per thousand yen10 g/dL compared to patients who had Hb < 10 g/dL for at least 1 month. However, Hb-var was not associated with mortality. In PD patients without hospitalization, intercurrent disease(s) or IV iron therapy, young age, higher albumin or RRF and lower CIMT were associated with greater oscillations in response to ESA therapy. Careful and appropriate ESA dose changes considering these parameters could minimize Hb variability in these patients.
Keywords: Hemoglobin variability; Peritoneal dialysis; ESA therapy; Mortality; ERYTHROPOIETIN RECEPTOR ACTIVATOR; CHRONIC KIDNEY-DISEASE; HEMODIALYSIS-PATIENTS; ANEMIA MANAGEMENT; LEVEL VARIABILITY; RENAL-DISEASE; MORTALITY; ASSOCIATIONS; IMPACT; ESRD